2021
DOI: 10.1111/omi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunization with recombinant GroEL plus CpG‐ODN inhibits Porphyromonas gingivalis‐induced inflammation and alveolar bone loss

Abstract: It has been reported that GroEL, a heat shock protein (HSP) produced by the representative periodontopathogenic bacterium, Porphyromonas gingivalis, induces inflammation-induced osteoclastogenesis and promotes alveolar bone resorption. In this study, we demonstrated the efficacy of a mucosal vaccine targeting GroEL against bone resorption induced by P. gingivalis. Female BALB/c mice received sublingual CpG oligodeoxynucleotide as an adjuvant with recombinant GroEL (rGroEL) prior to P. gingivalis exposure. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Consequently, HSP is viewed as a potential target for periodontal disease vaccines. Studies by Chang et al [ 12 ] and Lee et al [ 62 ] showed that immunization with HSP60 resulted in specific antibody responses, reducing inflammation and bone loss caused by Pg and other periodontal pathogens. This suggests that HSP60 could be a promising candidate for use as a vaccine against periodontal disease induced by various bacterial infections.…”
Section: Antigens Associated With Pg Vaccinementioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, HSP is viewed as a potential target for periodontal disease vaccines. Studies by Chang et al [ 12 ] and Lee et al [ 62 ] showed that immunization with HSP60 resulted in specific antibody responses, reducing inflammation and bone loss caused by Pg and other periodontal pathogens. This suggests that HSP60 could be a promising candidate for use as a vaccine against periodontal disease induced by various bacterial infections.…”
Section: Antigens Associated With Pg Vaccinementioning
confidence: 99%
“…CpG oligodeoxynucleotides (CpG-ODN) are synthetic molecules designed to stimulate TLR9 by mimicking bacterial DNA at CpG sites, activating the natural immune system through this pathway. Studies by Chang et al utilized rGroEL as an antigen and CpG-ODN as an adjuvant for the sublingual immunization of BALB/c mice, showing that CpG-ODN significantly increased levels of rGroEL-specific serum IgG and sIgA antibodies, suggesting that this strategy could be effective in preventing periodontal disease by inducing specific antibodies in mucosal and systemic systems [ 12 ]. Additionally, research by Liu et al [ 92 ] using OMP and Bai et al [ 14 ] using a periodontitis gene vaccine (pVAX1-HA2-fimA) demonstrated that CpG-ODN effectively induced a mucosal sIgA response, inhibited inflammation, and reduced bone loss.…”
Section: The Application Of Mucosal Adjuvants In Pg Vaccinementioning
confidence: 99%
See 2 more Smart Citations